Quantitative Proteomic Analyses of a Pathogenic Strain and Its Highly Passaged Attenuated Strain of Mycoplasma hyopneumoniae. (1st July 2019) - Li, Sha; Fang, Liurong; Liu, Wei; Song, Tao; Zhao, Fuwei; Zhang, Ruoxi; Wang, Dang; Xiao, Shaobo
Abstract : Mycoplasma hyopneumoniae is the causative agent of porcine enzootic pneumonia, a chronic respiratory disease in swine resulting in enormous economic losses. To identify the components that contribute to virulence and unveil those biological processes potentially related to attenuation, we used isobaric tags for relative and absolute quantification technology (iTRAQ) to compare the protein profiles of the virulent M. hyopneumoniae strain 168 and its attenuated highly passaged strain 168L. We identified 489 proteins in total, 70 of which showing significant differences in level of expression between the two strains. Remarkably, proteins participating in inositol phosphate metabolism were significantly downregulated in the virulent strain, while some proteins involved in nucleoside metabolism were upregulated. We also mined a series of novel promising virulence-associated factors in our study compared with those in previous reports, such as some moonlighting adhesins, transporters, lipoate-protein ligase, and ribonuclease and several hypothetical proteins with conserved functional domains, deserving further research. Our survey constitutes an iTRAQ-based comparative proteomic analysis of a virulent M. hyopneumoniae strain and its attenuated strain originating from a single parent with a well-characterized genetic background and lays the groundwork for future work to mine for potential virulence factors and identify candidate vaccine proteins.